The Influence of Talent Management and Knowledge Management on Teacher Innovation Performance at the SDIT Yaa Bunayya Gresik - Haqiqi, Syafrizal Mar’ie; Sukarni, Gendut (International Journal of Educational Research Excellence (IJERE), 2025)
This study investigates the impact of talent and knowledge management on the innovation performance of teachers at the Sekolah Dasar Islam Terpadu (SDIT) YAA BUNAYYA Gresik. Teachers play a crucial role in determining the quality of educational resources and their innovative performance is vital for advancing educational quality. Innovative performance involves the application of new practices and ideas to enhance education, which is heavily dependent on effective management strategies within the organization. Effective management to boost teachers' innovative performance includes the enhancement of both knowledge and talent management. Knowledge management refers to the systematic process of creating, acquiring, sharing, and utilizing knowledge to foster organizational learning and improve performance. When effectively implemented, this can lead to the generation of new ideas that drive innovation within educational institutions. On the other hand, talent management encompasses a range of human resource management activities aimed at processing and retaining an organization's human capital to maximize its output. This study used a sample of 35 principals and teachers from SDIT YAA BUNAYYA Gresik, applying the census method for data collection. Path analysis, supported by partial least squares (PLS) software, was employed to analyze the data. The results reveal that both talent and knowledge management have a positive and significant influence on teachers' innovation performance. These findings underscore the importance of talent and knowledge management as key factors in enhancing teachers' innovation performance. To optimize these aspects, school should focus on identifying, developing, and retaining teacher talent through systematic talent management processes. Additionally, schools should promote knowledge management practices such as knowledge sharing, organizational learning, and the effective use of information technology. In conclusion, improving teachers' innovation performance can be achieved comprehensively through strategic management of talent and knowledge